Effect of probiotic, prebiotic, and synbiotic supplementation on circadian clock in rats with fructose-induced non-alcoholic fatty liver - Coskun, Ayfer Beyaz; Turkoglu, Semra; Celep, Adviye Gulcin Sagdicoglu; Ozercan, Ibrahim Hanifi; Korkmaz, Engin (Springeropen, 2024)
BackgroundThe rate of NAFLD in the general population is estimated to be 25.2%. NAFLD is affected by lifestyle, diet, and inflammation. In this study, the use of probiotics, prebiotics, and synbiotics was aimed to modulate the circadian clock in the liver and improve metabolic disorder through the gut-liver axis.MethodsSix-week-old, healthy, 43 Wistar albino rats were included in the study and their average weight was determined as 140.50 g (95.00-177.00) at the beginning of the study. Before the study, the rats were randomly divided into 5 groups, 8 animals were placed in the 1st, 3rd, 4th, and 5th groups and 11 animals were placed in the 2nd group. Rats in group 1 were fed standard food for 13 weeks. Rats in the 2nd, 3rd, 4th, and 5th groups were fed with 10% fructose water during the 1-week adaptation period and then 20% fructose water. After the 7th week, probiotic treatment (2 x 109 CFU/ml Lactobacillus rhamnosus GG) was administered to rats in group 3rd via gavage for 6 weeks, and prebiotic treatment was administered to rats in group 4th with feed containing 10% grape seed extract. Rats in the 5th group were given a feed consisting of 10% grape seed extract and 2 x 109 CFU/ml Lactobacillus rhamnosus GG via gavage.ResultsIt was determined that the use of prebiotics as a treatment option in fatty liver had a more positive effect on glucose, ALT, melatonin, and ZO-1 values. In addition, it was observed that synbiotic use had more positive effects on histopathological findings, NAS score, and the expression level of circadian clock genes. While there was no significant difference between the mRNA levels of circadian clock genes, it was observed that gene expression levels increased with fructose consumption and decreased especially with synbiotic treatment.ConclusionIt has been observed that fructose modulates the circadian rhythm by affecting some biochemical and genomic pathways as a result of synbiotic use in order to prevent the negative effects of fructose on fatty liver.
Keywords: NAFLD; Circadian clock genes; Probiotic; Prebiotic; Symbiotic